Variação do custo efetivo em sementes florestais nativas - Graça, Keiti Elen Moura; Graça, Keiti Elen Moura (Universidade Federal de São Carlos, 2023)
The germination of a seed can be compromised by several factors. One of them is closelv related to storage time of the lot, thus, the conservations of any seed must be done under appropriate techniques to ensure physiological quality during sowing, making the most amount of seeds available in the lot. The study aimed to observe the variation in the germination rate as a function of the storage time of seeds, in relation to some types of pioneering species, in order to calculate the effective cost of each seed. The storage time of some species impaired germination, but in others it was not evident. Schinus terebinthifolia Raddi was a species that has very low germination values in the data analyzed compared to the literature, because it was noticed that the insect Megastigmus transvaalensis Hussey contaminates and prey seeds in the southeast region of Brazil. The results differed with seeds of some species that stored for a long time decreased the germination rate, increasing the effective cost per lot. Very small (PP) and small (P) seeds tended to have a less efficient germination rate, on the other hand, larger seeds (M) showed greater success in the percentages observed during the tests.
Effective cost variation in native forest seeds
Keywords: Armazenamento; Custo de sementes; Longevidade; Taxa de germinação; Germination rate; Longevity; Seed cost; Storage.; CIENCIAS AGRARIAS::RECURSOS FLORESTAIS E ENGENHARIA FLORESTAL